Grazing Habitat of the Rusa Deer (Cervus timorensis) in the Upland Kebar, Manokwari - FREDDY PATTISELANNO; AGUSTINA YOHANA SETYARINI AROBAYA (Biodiversitas Journal of Biological Diversity, 2009)
The general objective of the study was to provide current information on grassland communities as deer habitat and itsfuture development plan for a sustainable forage management in upland Kebar, Papua. Quantitative estimation of forage production was carried out by measuring a biomass harvest in fresh weight bases, while occasional observations on ranging deer were done within habitat range with the aid of 7x50 binoculars verified by actual visitation of grazed area. The study indicated Kebar, as the only grazing area of deer varies in low layer vegetation composition that comprised of eleven grass species and five legume species. Imperata cylindrica, Paspalum conjugatum, Themeda arguens, Melinis minutiflora and Cyperus rotundus were identified as food plant of deer in Kebar. Among these species T. arguens, M. minutiflora, C. rotundus and I. cylindrica were the most preferred species consumed by deer. The biomass harvest (species productivity) was 30.36 kg/ha fresh weight, while deer food productivity in the grassland was slightly lower (26.70 kg/ha) than total productivity of the grassland. The major drainage area is Kasi River, but two other rivers across this valley (Api River, Apriri River) are also supply water to the swampy area.Key words: grazing, habitat, Rusa, Kebar, Manokwari.